New in pediatric neurodietology - V. M. Studenikin (Лечащий Врач, 2021)
Modern childhood neurodietology affects so many neurological and somatoneurological conditions that it would not be entirely correct to focus on some of them and ignore the rest. Epilepsy, migraine and headache, neurometabolic diseases, hereditary neuromuscular pathology, demyelinating and autoimmune diseases of the central nervous system, sleep disorders, as well as behavioral disorders – all of them are not a complete list of conditional «targets» of neurodietology. Its role in the formation of an adequate cognitive and emotional development of the individual is also important, which is of particular importance in childhood. It should be noted that neurodietology and approaches to the choice of therapeutic nutrition every year occupy an increasingly strong position in the world of clinical medicine. Russian and foreign basic publications of recent years are considered in the review of literature, dedicated to neurodietological and nutritional therapy issues for neurological diseases and pathological disorders in patients of pediatric age. Attention deficit/hyperactivity disorder, stroke, migraine, headaches, sleep disorders, epilepsy, glycogen storage disease type VII (fructokinase deficiency), multiple sclerosis, variable neuromuscular pathologies (spinal muscular atrophy – SMA and others), as well as various neurometabolic disorders (methylmalonic acidemia, propionic acidemia, isovaleric acidemia, mitochondrial cythopathies) etc. can be listed among above-mentioned nosological forms of pathology. The role of neurodietology is stressed in particular for stimulation of neurocognition development in infants and children of various age groups. Variability of nutritional approaches to practical management of neurological disorders in patients of pediatric age reflects the versatility of contemporary neurodietology.